Sorption of basic dyes by Hydrilla verticillata - Low, K.S.; Lee, C.K.; Heng, L.L. (Taylor and Francis Group, 1994)
The potential of an aquatic plant, Hydrilla verticillata, to remove two basic dyes, methylene blue and basic blue, from aqueous solutions was assessed under various experimental conditions. Results showed that dried Hydrilla was able to remove the dyes efficiently and rapidly. Its reakthrough time under flow conditions could be predicted using Hutchin's bed depth-service time (BDST) model. As Hydrilla is readily available, it could represent a cheap source of biosorbent for basic dyes.